Propagação de sapotizeiro (Manilkara zapota L.) por estaquia - de Almeida, Eduardo Jose [UNESP]; Geraldo Martins, Antonio Baldo [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
Two sapoti tree accesses (Manilkara zapota), native plants of south of Mexico and of America Central, belonging to the Collection of Fruitful Native and Exotic of UNESP/FCAV, Jaboticabal Campus, was studied with relationship to the cutting propagation. The first test consisted of fast immersion of cutting base semi-herbaceous foliage of selected accesses FCAV-III and FCAV-VII. The ttreatments were alcoholic solution (50%) of indolbutiric acid (IBA) in concentrations of 0, 1,000, 3,000, 5,000 and 7,000 mgL(-1). and the cuttings preparing with and without latex exudate washing for a period of 14 hours in recipient with pure water. This trial was set in 5 x 2 x 2 factorial scheme (IBA concentrations x accesses x cutting preparation) The second test consisted the herbaceous foliage immersion of FCAV-III access in IBA concentrations above. Both experiments were distributed in randomized design with four replications and 10 cuttings each. All cuttings were collected in spring and prepared with about 12 cm of length, planted in medium texture vermiculite and carried under conditions intermittent mist spray flashing in chamber with 50% light. The two accesses tested not rooted and treatments were not able to induce the roots emission.

Dois acessos de sapotizeiro (Manilkara zapota), planta nativa do sul do México e da América Central, pertencentes à Coleção de Frutíferas Nativas e Exóticas da UNESP/FCAV, Campus de Jaboticabal foram estudados quanto à propagação por estaquia de ramos coletados na primavera. O primeiro ensaio consistiu de imersão rápida da base de estacas semi-herbáceas enfolhadas dos acessos selecionados denominados FCAV-III e FCAV-VII, em solução hidroalcoólica (50%) de ácido indolbutírico (AIB) nas doses 0, 1.000, 3.000, 5.000 e 7.000 mgL-1. Foi testado o preparo de estacas com e sem lavagem do látex exsudado, em recipiente contendo água pura por período de 14 horas. O segundo ensaio constou somente da imersão das estacas herbáceas enfolhadas do acesso FCAV-III nas doses de AIB acima mencionadas. Ambos os ensaios foram realizados com estacas coletadas na primavera e preparadas com cerca de 12 cm de comprimento, plantadas em vermiculita textura média e conduzidas em condições de câmara de nebulização por aspersão intermitente sob telado com 50 % de luminosidade. Utilizaram-se quatro repetições com 10 estacas cada. O delineamento foi inteiramente casualizado e o primeiro ensaio foi conduzido em esquema fatorial 5 x 2 x 2 (doses de AIB x acessos x preparo das estacas) e ambos os ensaios foram analisados pelo teste de Tukey. Os dois acessos testados não apresentaram significativo enraizamento e os tratamentos utilizados não foram capazes de induzir apreciável emissão de raízes.
Propagation of sapoti tree (Manilkara zapota L.) for cutting
Keywords: Exotic fruit; Rooting; Vegetal regulation; Auxin